Clinical significance of prophylactic central compartment neck dissection in the treatment of clinically node-negative papillary thyroid cancer patients. Issue 1 (December 2016) - Gambardella, Claudio; Tartaglia, Ernesto; Nunziata, Anna; Izzo, Graziella; Siciliano, Giuseppe; Cavallo, Fabio; Mauriello, Claudio; Napolitano, Salvatore; Thomas, Guglielmo; Testa, Domenico; Rossetti, Gianluca; Sanguinetti, Alessandro; et al.
Abstract Background Lymph nodal involvement is very common in differentiated thyroid cancer, and in addition, cervical lymph node micrometastases are observed in up to 80 % of papillary thyroid cancers. During the last decades, the role of routine central lymph node dissection (RCLD) in the treatment of papillary thyroid cancer (PTC) has been an object of research, and it is now still controversial. Nevertheless, many scientific societies and referral authors have definitely stated that even if in expert hands, RCLD is not associated to higher morbidity; it should be indicated only in selected cases. Main body In order to better analyze the current role of prophylactic neck dissection in the surgical treatment of papillary thyroid cancers, an analysis of the most recent literature data was performed. Prophylactic or therapeutic lymph node dissection, selective, lateral or central lymph node dissection, modified radical neck dissection, and papillary thyroid cancer were used by the authors as keywords performing a PubMed database research. Literature reviews, PTCs large clinical series and the most recent guidelines of different referral endocrine societies, inhering neck dissection for papillary thyroid cancers, were also specifically evaluated. A higher PTC incidence was nowadays reported in differentiated thyroid cancer (DTC) clinical series. In addition, ultrasound guided fine-needle aspiration citology allowed a more precocious diagnosis in the early phases of disease. The role of prophylactic neck dissection in papillary thyroid cancer management remains controversial especially regarding indications, approach, and surgical extension. Even if morbidity rates seem to be similar to those reported after total thyroidectomy alone, RCLD impact on local recurrence and long-term survival is still a matter of research. Nevertheless, only a selective use in high-risk cases is supported by more and more scientific data. Conclusions In the last years, higher papillary thyroid cancer incidence and more precocious diagnoses were worldwide reported. Among endocrine and neck surgeons, there is agreement about indications to prophylactic treatment of node-negative "high-risk" patients. A recent trend toward RCLD avoiding radioactive treatment is still debated, but nevertheless, prophylactic dissections in low-risk cases should be avoided. Prospective randomized trials are needed to evaluate the benefits of different approaches and allow to drawn definitive conclusions.